METODE TERAPI RUQYAH SYAR’IYYAH DALAM MENGATASI GANGGUAN KEJIWAAN PADA PASIEN DI KLINIK HAMDALAH KELURAHAN TOMBOLO KECAMATAN SOMBA OPU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal aims to describe how the implementation of ruqyah syar'iyyah therapy in overcoming mental disorders. This study uses a qualitative type of research located at the Hamdalah Clinic, Tombolo Village, Somba Opu District, Gowa Regency. The research approach used is the Islamic Guidance and Counseling approach and the Psychology approach. The results of this study indicate the factors causing mental disorders in patients at the Hamdalah Clinic, Tombolo Village, Somba Opu District, Gowa Regency, namely: Disease factors, family factors, and work factors. In the process of implementing syar'iyyah ruqyah therapy in overcoming mental disorders, there are three stages, namely the preparation stage which includes registration at the cashier, preparing the ruqyah place, the patient is encouraged to perform ablution and analyzing the patient's condition by asking for several questions. The stages of implementation using the method of reading the holy Qur'an are carried out by the therapist by reading the verses of ruqyah. The stages after therapy are giving advice/da'wah to patients to further increase worship of Allah SWT.